Credibility and bias: The case for implementing both a debt anchor and a balanced budget rule - Marcela de Castro-Valderrama; Nicolás Moreno-Arias; Juan José Ospina-Tejeiro (Graduate Institute of International and Development Studies, 2023)
Should a government have more than one fiscal rule constraining fiscal aggregates? If so, why? In this paper, we present a dynamic general equilibrium model of a small open economy featuring an incumbent government to assess how and why implementing a budget balance rule and a debt anchor rule is non-redundant and welfare-improving. Our findings suggest that the implementation of a combination of fiscal rules is optimally preferred over a single rule, as each rule has a different effect on credibility and fiscal behaviour. While the debt anchor rule prevents the propagation of the negative effects of imperfect fiscal credibility, the operational rule reduces amplification by avoiding overindebtedness and minimizing the welfare-detrimental effects arising from a deficit-biased government.
Keywords: E61; E62; H60; H63; F41; 330; Fiscal Rules; Credibility; Deficit Bias; Balanced Budget Rule; Debt Anchor Rule; Fiscal Policy; Welfare